Ethical Communication in Humor: Analyzing Panji's Stand-Up Comedy to Raise ECO-Cultural Awareness - Nabilah Siti Haniyah; Rita Hartati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Stand-up comedy has evolved into a dynamic platform for the treatment of complex social and environmental issues, combining entertainment and education. However, little is known about how stand-up comedians manage the balance between entertainment, education, and ethical responsibility when addressing environmental challenges. This study aims to understand how humor functions as a tool for raising environmental cultural awareness and promoting positive behavioral changes. The study employs a case study methodology in conjunction with a qualitative approach. The analysis will be carried out through discourse analysis to uncover the underlying themes, ethical considerations, and communication techniques embedded in Pandji Pragiwaksono's humor. The findings from this study will not only enhance our understanding of humor's role in environmental communication but also provide practical insights for comedians, environmental educators, and communicators who are trying to effectively engage audiences while maintaining ethical integrity across different cultural contexts.